Attitude of Media Tribunbengkulu.Com in Reporting on Fuel Price Policy - Losiana Losiana; Sapta Sari; Yanto Yanto (Penerbit Jurnal Indonesia, 2023)
The increase in subsidized fuel prices is one of the problems that is of concern to all levels of society, especially for those who use subsidized fuel oil as their main fuel. This of course attracted the attention of the media team to make this issue a topic of news. The news presented can be seen from different perspectives in each media. This research was conducted to find out how the attitude of the TribunBengkulu.com media in reporting the fuel price policy was analyzed through its reports. The analysis used is Robert N.Etman's Framing Analysis which consists of four elements, namely Define Problems, Diagnose Cause (estimate the causes of problems), Make Moral Judgments (make moral decisions), and Treatment Recommendations (Emphasize resolution). The results of the study show that most of the reporting from TribunBengkulu.com is dominated by news that is more supportive of the government. It is very rare for TribunBengkulu.com to publish information that is inconsistent with government information, such as information about people's rejection of the fuel subsidy increase policy. On the other hand, TribunBengkulu.com is playing it safe by reporting plans to increase subsidized fuel prices.